PENGELOLAAN MANAJEMEN PEMBINAAN GARJAS PASIPAMOPS DALAM MENINGKATKAN NILAI TES KESEGARAN JASMANI SERSAN TARUNA DI BATALYON TARUNA DEWASA - Indiarto Kusno Hadi; Aris Basuki; Sopiin; Muhamaad Raindra; Mohamad Irul ferdiyansyah (PPM Sdirjianbang Akademi Militer, 2024)
According to the standards contained in the Military Academy, all cadets of the Military Academy including cadets Level II/Sertar are required to have a good basic tripola, ranging from qualified academics, good personality and excellent physical fitness. However, in the implementation in the field, there are still found some cadets Level II / Sertar who have problems in the physical field, especially the value of the physical freshness Test (TKJ). Based on the data from the TKJ results of the first semester of Sergeant cadets in 2023, there were 190 cadets who received TKJ grades with very good predicates (BS), 221 Cadets with good predicates (B), 13 cadets could not participate in activities due to illness, and 1 Cadet who did not graduate or did not meet the requirements set by the institution. In addition to the data already mentioned, there are 13 cadets whose pull-up value is below 10 movements (below the standard set by the adult Cadet Battalion). The purpose of this study was to convey concepts and ideas after the management of Management, Management effort constraints Pasipamops in increasing the value of physical freshness Test Sergeant cadets in Battalion cadets adults. research method is defined as a scientific way to obtain data with a specific purpose and usefulness. In addition, the research method is a way to conduct an investigation using certain ways that have been determined to obtain scientific truth, so that later the research can be accounted for. Advise the battalion commander of adult cadets through Pasipamops Battalion of adult cadets in order to provide a measurable and targeted physical refresher training schedule to the sergeant cadets and reschedule the physical refresher training schedule.